Stress-relaxation and fatigue behaviour of synthetic brow-suspension materials. (February 2015) - Kwon, Kyung-Ah; Shipley, Rebecca J.; Edirisinghe, Mohan; Rayment, Andrew W.; Best, Serena M.; Cameron, Ruth E.; Salam, Tahrina; Rose, Geoffrey E.; Ezra, Daniel G.
Abstract: Ptosis describes a low position of the upper eyelid. When this condition is due to poor function of the levator palpebrae superioris muscle, responsible for raising the lid, "brow-suspension" ptosis correction is usually performed, which involves internally attaching the malpositioned eyelid to the forehead musculature using brow-suspension materials. In service, such materials are exposed to both rapid tensile loading and unloading sequences during blinking, and a more sustained tensile strain during extended periods of closure. In this study, various mechanical tests were conducted to characterise and compare some of commonly-used synthetic brow-suspension materials (Prolene ®, Supramid Extra ® II, Silicone rods (Visitec ® Seiff frontalis suspension set) and Mersilene ® mesh) for their time-dependent response. At a given constant tensile strain or load, all of the brow-suspension materials exhibited stress-relaxation or creep, with Prolene ® having a statistically different relaxation or creep ratio as compared with those of others. Uniaxial tensile cyclic tests through preconditioning and fatigue tests demonstrated drastically different time-dependent response amongst the various materials. Although the tests generated hysteresis force–strain loops for all materials, the mechanical properties such as the number of cycles required to reach the steady-state, the reduction in the peak force, and the cyclic energy dissipation varied considerably. To reach the steady-state, Prolene ® and the silicone rod required the greatest and the least number of cycles, respectively. Furthermore, the fatigue tests at physiologically relevant conditions (15% strain controlled at 6.5 Hz) demonstrated that the reduction in the peak force during 100, 000 cycles ranged from 15% to 58%, with Prolene ® and the silicone rod exhibiting the greatest and the least value, respectively. Many factors need to be considered to select the most suitable brow-suspension material for ptosis correction. These novel data on the mechanical time-dependent performance could therefore help to guide clinicians in their decision-making process for optimal surgical outcome. Graphical abstract: Highlights: Mechanical behaviour of synthetic brow-suspension materials was investigated. Stress-relaxation properties of the materials have been compared. Fatigue of the materials was studied in physiologically relevant conditions. The findings have direct clinical implications in ptosis surgical outcome.